The Role of the National Commission on Disability in Promoting Business Inclusion for Persons with Disabilities in Indonesia - Andi Muhammad Rivai; Siti Syarifah Wafiqah Wardah; Yusi Irensi Seppa (Cita konsultindo, 2025)
This study analyzes the role of the National Disability Commission in promoting business inclusivity for persons with disabilities in Indonesia. Based on Law No. 8 of 2016, the National Disability Commission serves to ensure the fulfillment of the rights of persons with disabilities, particularly access to employment and entrepreneurship. Using a descriptive qualitative method, this study found three main roles of the National Disability Commission: policy advocacy, cross-sector collaboration, and empowerment through training and public campaigns. Key challenges include weak coordination, limited authority, and social stigma. The National Disability Commission functions as a moral parliament that strengthens the bargaining position of persons with disabilities in the world of work and has the potential to be a catalyst for transformation towards an inclusive and equitable employment ecosystem.